POSTCOLONIAL AEROMOBILITIES branding, cultural governance and tourism imageries. (ROUTLEDGE, 2025)
This edited collection explores how national airlines in postcolonial states operate at the complex intersection of corporate branding, cultural governance, tourism development, and national identity formation. It conceptualizes airplanes and airports as both tangible infrastructural spaces and symbolic domains that connect geographically distant regions while embodying aspirations of political sovereignty and cultural unity. Through diverse case studies spanning multiple continents, the book examines how commercial aviation's physical and cultural spaces either reinforce or challenge colonial histories and imperial legacies.The volume reveals how modern Western imperial narratives were shaped through specific cultural and social negotiations that played out in airline branding, route networks, service standards, and cultural policies. It analyzes how airlines serve as vehicles for projecting soft power and cultural diplomacy while mediating between local traditions and global modernity. Drawing on rich empirical examples from Angola, Argentina, Australia, Belgium, Brazil, Jamaica, Kenya, France, Hong Kong, Indonesia, Lebanon, Mexico, Peru, South Africa, Turkey, and the United States, this collection demonstrates how airlines employ sophisticated cultural management and corporate branding strategies to shape national and regional identities.By examining airlines as sites where business strategy, cultural policy, and identity politics intersect, this collection advances our understanding of how transportation infrastructure shapes social imaginaries and power relations in our increasingly connected yet culturally diverse world. The research has important implications for scholars of business history, cultural studies, postcolonial theory, and transportation geography while offering practical insights for policymakers and airline industry leaders.